Synthesis and characterization of the hybrid Ni-TiO2/PANI for an efficient hydrogen photoproduction under visible light (Sciences & Technology. A, exactes sciences, 2014)
NixZn1-xO/Polyaniline hybrid photocatalysts are synthesized by the impregnation method at ambient temperature and used for hydrogen photoproduction experiments. XRD, UV-Vis DRS, SEM and TGA are used to characterize the prepared materials. It is shown that the Ni2+ amount doped into ZnO controls its morphology and enhances its photoactivity for H2 generation. Polyaniline (PANI) is shown to sensitize ZnO and to extend its light absorption toward the visible region. The hybrid photocatalyst with 10 mol. % Ni2+ and 10 wt. % PANI shows the maximum photocatalytic H2 production for one hour of visible irradiation: ~ 558 μmole while only ~ 178 μmole in the presence of pure ZnO. It is also observed that the hydrogen photoproduction efficiency depends strongly on the nature of the sacrificial electron donor and increases in the order: thiosulfate >sulfide> propanol.